The Effects of Roller Massage, Massage, and Ice Bath on Lactate Removal and Delayed Onset Muscle Soreness - Soetanto Hartono; Achmad Widodo; Himawan Wismanadi; Gulbuldin Hikmatyar (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2019)
The purpose of the study was to investigate the effects of rolling massage, massage, and ice bath on lactate removal and delayed onset muscle soreness. Thirty students of Faculty of Sport Sciences of third semester were randomly selected and assigned to three groups, roller massage, massage, and ice bath group. All groups were doing Running-based Anaerobic Sprint Test (RAST) after 10 minute warm up. Eight minutes after RAST, all students were examined their blood lactate using blood lactate analyzer. The roller massage group was treated using foam roller for 5 minutes, , the massage group was massaged for 5 minutes, the ice bath group were put in 10 degree cold water for 5 minutes, then their blood lactate were reexamined. The normality test of roller massage is .022, and homogeinity test p=.133, so the data was analized using nonparametric Kruskal Wallis. Contrary to results of other studies, lactate removal tends to be the most effective in ice bath treatment (17.40) compared with massage treatment (16.65), and roller massage (12.45), and reduction in Delayed Onset Muscle Soreness (DOMS) tends to be most effective in ice bath treatment (12.25) compared with massage treatment (13.95), and roller massage (20.30) eventhough non significant (p=.399). Vasoconstriction effect of ice bath made a faster lactate removal, physique trait also might have an effect. Cooling effect of ice bath has an effective analgetic effect.